Strategi Kesantunan Berbahasa Mahasiswa kepada Dosen pada Wacana Komunikasi Media Sosial Whatsapp - Sriyanti, Rini (UNIVERSITAS SERAMBI MEKKAH, 2024)
This study examines the politeness strategies employed by students when communicating with lecturers via the social media platform WhatsApp. Based on a literature review, it was found that students tend to apply positive politeness strategies by using warm greetings, formal language, and politeness markers such as